The way of modeling of spatials structure of protein on determining it nucleotide sequences - Sokolik, V. V. (Biophysical Bulletin, 1970)
The novel way of modeling the spatial structure of a protein in determining its nucleotide sequences iselaborated. The concept of a configuration of peptide bond as the major coded in genome alongside withamino acids by the rests, an element of the spatial structure of the protein. The table of a genetic code of the spatial structure of the protein is presented, using which it is possible to construct a structural template of protein, and also to decode the presence and position of fragments of the secondary structure of it. The important advantage of a method is that it is possible to construct a structural pattern individually for any unknown protein only "having read through" determining its nucleotide sequence. The lead comparative analysis of schemes of secondary structure, decoded on nucleotide sequences, and schemes from Protein Data Bank, constructed on the basis of experimental data of spectroscopy of a nuclear magnetic resonance and the roentgen-structural analysis, for α-subunit of hemoglobin, major actinandα-actin 1 testified to greater resolvability (up to 1 amino acids rest), accuracy (100 %), unambiguity (an individual structural pattern) and simplicity of the way of modeling offered in given work.